Biomass and abiotic variables change in phytotelmic environment in the tank-bromeliad Nidularium longiflorum Ule in tropical forest - Neves,Karina Margaret Silva das (2019)
Abstract Aim Phytotelm plays an important role in plant growth and ecosystem functioning, but this natural aquatic microcosm is poorly known. We evaluated the seasonal (dry and rainy seasons) and spatial variations (forest trail and stream sites) of the phytotelm in Nidularium longiflorum, bromeliad that occurs in the Atlantic Forest. Methods Abiotic and biotic variables were measured in tank-bromeliad phytotelms. The biomass was analyzed by ash-free dry mass and chlorophyll-a concentration. Results Abiotic variables measured in the phytotelmic environment of bromeliads varied between sampling sites and seasons. Temperature, electrical conductivity and total nitrogen values were significantly different between seasons and sites. Chlorophyll-a and ash-free dry mass (organic matter) in phytotelm were significantly different between sampling sites. Eleven genera of algae in the phytotelm were identified. PCA axis 1 ordination evidenced the seasonal variation of environmental conditions. Conclusions Our findings suggest that environmental and micro-environmental conditions do not favor the development of algal community in the phytotelm. Biomass and abiotic variables in phytotelm of Nidularium longiflorum change seasonally, however biomass accumulation was strongly influenced by site characteristics.